PENERAPAN LANGUAGE SKILLS MELALUI COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRD) DALAM PEMBELAJARAN BAHASA DI MA NEGERI 1 KERINCI - Nuzmi Sasferi (Tarbawi : Jurnal Ilmu Pendidikan, 2018)
Language skills can be improved through the application of CIRC learning models, and the procedure of CIRC includes: teacher presentation, team practice, individual practice, peer preassessment, additional practice and testing. Then the last one is various activities which they elements in the CIRC learning model such as (1) reading each other's stories with group friends, (2) conclude stories, (3) listen to stories, (4) retell stories that have been read and heard in oral and written forms, (5) play drama, (6) write, edit, revise, and publish poetry with group friends.